Addressing challenges in serial 10 gigabytes multimode fiber enterprise networks. - Babla, Chet
As the number of networked computer devices connected within local area networks increases, the aggregation requirements of the optical fiber backbone within these networks are also increased. This article highlights the challenges - and a possible solution - to migrating data communications networks to higher data rate capability, while in parallel cost effectively supporting the existing fiber infrastructure.
Keywords: 10Gbit/s.; data communications network; local area network; multimode fiber enterprise network; optical fiber backbone